Pengembangan E-Modul Berbasis Flipbook pada Materi PPKn Kelas IV Sekolah Dasar - Elmilia; Syarifuddin, Ahmad; Hamzah, Amir; Faisal; Shawmi, Ayu Nur (Limas PGMI, 2024)
This study aims to produce a Flipbook-based E-Module and evaluate its validity and practicality in learning Civics grade IV at SDN 09 Lubuk Keliat Ogan Ilir. Using the 4-D development model by Thiagarajan, this research involves the Define, Design, Develop, and Dissemination stages with the trial subjects being one teacher and 27 students. The instruments used included validation sheets for material, media, and language experts, as well as practicality sheets for teachers and students. The research was conducted from 2 to 7 March 2024. The results of the validity assessment showed that the E-Module obtained an excellent average score: 89.28% from material experts (very valid), 96.42% from media experts (very valid), and 97.22% from language experts (very valid). Positive responses from teachers reached 97.5% (very practical), while students reached 95.8% (very practical). These findings indicate that the Flipbook-based E-Module is feasible and practical for use in Civics learning. As a follow-up, the E-Module will be applied in routine learning and teachers will be trained to maximise its use. Further research is recommended in other schools to test the effectiveness of the E-Module in different contexts and develop additional features to enhance students' learning experience.